The Use of ‘Omics for Diagnosing and Predicting Progression of Chronic Kidney Disease: A Scoping Review - Govender, Melanie A.; Brandenburg, Jean-Tristan; Fabian, June; Ramsay, Michèle (Frontiers in Genetics, 2021)
Globally, chronic kidney disease (CKD) is an emerging public health problem. Various ‘omics platforms have been used to provide insights into the molecular basis of kidney dysfunction. This scoping review is a synthesis of the current literature on the use of different ‘omics platforms to identify pathophysiological processes leading to CKD and to detect biomarkers that could be used to detect early-stage CKD and predict disease progression. This review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews protocol. Seventy-six studies published from January 2007 to May 2020 were included following a structured selection process. The proteomic approach was the most common ‘omic platform (n=41), followed by metabolomics (n=22), genomics (n=5), epigenomics (n=3), transcriptomics (n=2) and three studies used a combination of ‘omics platforms. The majority of studies (n=58) reported on CKD associated with diabetes mellitus. Fourteen studies that provided information on the pathogenic mechanisms of CKD and biomarkers that play a role in early detection are discussed. These biomarkers were mainly used to detect CKD and predict progression in European populations, highlighting the need for ‘omics research in African populations since disease etiologies may differ across ethnic groups. To assess the transferability of findings, it is essential to do research in diverse populations.